Climate study in different phases of medical students of medical colleges of Bangladesh - Nahar, Nurun; Talukder, Md Humayun Kabir; Khan, Md Tafazzal Hossain; Nargis, Tahmina; Mohammad, Shegufta; Akhter, Nasrin (Bangladesh Journal of Medical Education, 2012)
Climate is the soul and spirit of medical college and students experiences of the climate are a useful basis for modifying and improving the quality of educational environment. The present study was undertaken to identify how the students perceive the educational environment in a newly restructured curriculum using the Dundee Ready Education Environment Measure (DREEM). The inventory was administered to 1903 medical students (3rd, 4th and 5th year) of MBBS course adopting purposive sampling. The mean DREEM total score and mean score for five essential domains were found significantly different in different phase of medical students. DREEM total score were found to be highest for 3rd year students (119/200) and lowest for 5th year students (105/200) but all the three groups of students perceive the environment as positive. 3rd year students also scored high than 4th and 5th year students in five domains. All the three groups of students identify problems in environment and give opinion that there are many issues need to improve with special attention to perception of atmosphere and social self perception. The results are the first data obtained from the students about the educational environment and give important feedback to curriculum planners and change managers of the faculty for necessary improvement. DOI: http://dx.doi.org/10.3329/bjme.v1i1.12856 Bangladesh Journal of Medical Education Vol.1(1) 2010 pp.29-36